All-hexahedral mesh smoothing with a node based measure of quality - Calvo, Nestor Alberto (2001)
This research work deals with the analysis and test of a normalized-Jacobian metric used as a measure of the quality of all-hexahedral meshes. Instead of element qualities, a measure of node quality was chosen. The chosen metric is a bound for deviation from orthogonality of faces and dihedral angles. We outline the main steps and algorithms of a program that is successful in improving the quality of initially invalid meshes to acceptable levels. For node movements, the program relies on a combination of gradient-driven and simulated annealing techniques. Some examples of the results and speed are also shown.